The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1590/s0103-73312015000100011
|View full text |Cite
|
Sign up to set email alerts
|

Democracia e conquista: Saúde Mental como política pública municipal

Abstract: A Reforma Psiquiátrica brasileira é parte integrante da construção da democracia no Brasil e a Constituição Nacional de 1988 marca a descentralização política e financeira em direção aos municípios da federação. A pesquisa é qualitativa e objetiva analisar o processo democrático de construção, implantação e a aplicabilidade de uma Lei Municipal de Saúde Mental frente às contradições do processo social de reforma psiquiátrica brasileiro. Metodologia: triangulação de dados entre entrevistas com gestores (2), tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…A research that sought to analyze the democratic process of construction, implantation and applicability of the Lei Municipal de Saúde Mental de Alegrete (freely translated as Municipal Mental Health Law of Alegrete), Rio Grande do Sul, showed that this is necessary for legal guarantee of rights, but only makes sense if added to the history of psychiatric reform in order to bring new health workers closer to the meaning of social movements such as psychiatric reform (24) .…”
Section: Discussionmentioning
confidence: 99%
“…A research that sought to analyze the democratic process of construction, implantation and applicability of the Lei Municipal de Saúde Mental de Alegrete (freely translated as Municipal Mental Health Law of Alegrete), Rio Grande do Sul, showed that this is necessary for legal guarantee of rights, but only makes sense if added to the history of psychiatric reform in order to bring new health workers closer to the meaning of social movements such as psychiatric reform (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Artículos respuesta al marco regulatorio promueve la participación promueve la democracia incrementa la eficiencia en la asignación de recursos mejora las capacidades y prácticas de gestión (Avelino, Barberia, & Biderman, 2014) x (Gerigk & Pessali, 2014) x x (da Silva et al, 2014) x x (Jesus, & Teixeira, 2014) x (Duarte et al, 2015) x (L. Santos & Campos, 2015) (Vargas et al, 2015) x x x (Filippon, Kantorski, & Saeki, 2015) x (Mazon, Mascarenhas, & Dallabrida, 2015) x (Barreto Junior, 2015) x x x (Albuquerque et al, 2015) x x Fuente: elaboración propia…”
Section: Apéndice Bunclassified